Mechanical behaviors and acoustic emission fractal characteristics of coal specimens with a pre-existing flaw of various inclinations under uniaxial compression - Li, Dexing; Wang, Enyuan; Kong, Xiangguo; Ali, Muhammad; Wang, Dongming (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2019)
To study the influence of hydraulic slotting inclination on the mechanical behaviors of coal seam during mining process, uniaxial compression experiments on coal specimens with a single pre-existing flaw inclined at 0°, 15°, 30°, 45°, 60°, 75°, 90° and intact specimens were conducted. Acoustic emission (AE) signals in the loading process were monitored, and fractal analysis method was introduced to investigate the AE characteristics. Additionally, the laboratory experiments were simulated by a finite element code. Both the experimental and numerical results show that the existence of a flaw reduces the mechanical properties of coal. The uniaxial compressive strength and modulus of elasticity increase polynomially and linearly with the increase of inclination angle, respectively. When the coal specimen ruptures finally, the fewer the surface secondary cracks or the more the sudden drops of stress, the smaller the peak value of AE count. According to the stress–strain curve, the loading process is divided into five stages: (I) compaction stage; (II) linear elastic stage; (III) stable crack propagation stage; (IV) accelerating crack propagation stage; (V) post peak and residual stage. AE fractal characteristics in various stages of each specimen were determined by Grassberger and Procaccia algorithm based on phase space reconstruction theory. AE count show fractal characteristics from stage III. The fractal dimension declines rapidly in stage IV, and continues to decline further or rise slightly in stage V, but both are lower than that in stage III. Therefore, the changing rule of AE fractal dimension in different loading stages can be used as a precursor to coal and rock dynamic disasters.